2021
DOI: 10.5194/amt-14-1511-2021
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the height of the turbulent mixing layer from data of Doppler lidar measurements using conical scanning by a probe beam

Abstract: Abstract. A method is proposed for determining the height of the turbulent mixing layer on the basis of the vertical profiles of the dissipation rate of turbulent energy, which is estimated from lidar measurements of the radial wind velocity using conical scanning by a probe beam around the vertical axis. The accuracy of the proposed method is discussed in detail. It is shown that for the estimation of the mixing layer height (MLH) with the acceptable relative error not exceeding 20 %, the signal-to-noise rati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Boundary layer height estimation algorithms (Tucker et al, 2009;Berg et al, 2017;Bonin et al, 2018) purely using the Doppler lidars are limited by the range of the Doppler lidars at the ARM SGP facility, which may or may not reach the top of the boundary layer. The data availability of the ARM Doppler lidar SGP C1 systems is typically less than 1-2 km (Newsom and Krishnamurthy, 2020), and the data availability of the Doppler lidar vertical stares and velocity azimuth display scans for the study period are shown in Appendix A.…”
Section: Preliminary Data Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Boundary layer height estimation algorithms (Tucker et al, 2009;Berg et al, 2017;Bonin et al, 2018) purely using the Doppler lidars are limited by the range of the Doppler lidars at the ARM SGP facility, which may or may not reach the top of the boundary layer. The data availability of the ARM Doppler lidar SGP C1 systems is typically less than 1-2 km (Newsom and Krishnamurthy, 2020), and the data availability of the Doppler lidar vertical stares and velocity azimuth display scans for the study period are shown in Appendix A.…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…The data availability of the ARM Doppler lidar SGP C1 systems is typically less than 1-2 km (Newsom and Krishnamurthy, 2020), and the data availability of the Doppler lidar vertical stares and velocity azimuth display scans for the study period are shown in Appendix A. The Tucker method z i is used for inter-comparison with the RF model in this study, primarily due to its ease in application to the multi-year dataset and known performance, including its established usage in studies using the ARM Doppler lidar and other locations and instruments (Träumner et al, 2011;Shukla et al, 2014;Schween et al, 2014;Berg et al, 2017;Lareau et al, 2018;Lareau, 2020). Vertical velocity variance profiles provided in the sgpdlprofwstats4newsC1.c1 VAP and a variance threshold of 0.04 m 2 s −2 are used to determine z i , following Tucker et al (2009).…”
Section: Preliminary Data Analysismentioning
confidence: 99%
See 3 more Smart Citations